Analysis of blood flow in abdominal aortic aneurysm using computational fluid dynamic - Mohd Yusuf, Mohd Jaafar (2009)
Aneurysm is an abnormalities occurs in blood vessel that involve the size increment and dilations where the cause of the disease not yet been founded. Abdominal aortic aneurysm was occurring at abdomen aorta. The abnormal diameter size of abdominal aorta was cause by ballooning or bulge that lead to changes in blood flow behavior. Investigation on the behavior of blood flow in abdominal aortic aneurysm was taken place to determine the pressure distribution and velocity profile in the aneurysm region. The diameter of normal aorta was 20 mm and the diameter of aneurysm aorta was considered as 60 mm from the literature. The flow of blood in aorta will be disturbed when the diameter of aorta was changed. Aneurysm is acting like diffuser that increases the pressure and decreases the velocity when blood entering the aneurysm region. Oppositely when it leaving the aneurysm the pressure wills decreases back and the velocity will be increase like nozzle. It was proved that the flow behavior inside aneurysm region would be different compared to the normal aorta from the previous study. The size of aorta influences the pressure and velocity of blood. The flow inside aneurysm region was disturbed due to pressure and velocity changes and resulting the formation of vortex. Reynolds number was establishing by using different initial velocity of blood flow and different diameter of aorta. The simulation of the model was studied under incompressible and non-Newtonian condition which investigated computationally by fluid dynamic software. The studies was done without experiment set-up but based on numerical approach only.